How convergent and divergent signaling pathways are mediated by card-card interactions - Qin, Gong (Nanyang Technological University, 2020)
PRRs play an essential role in detecting pathogenic infections and propagating such immune signals to downstream effectors. NLRs act as a classic subfamily of PRRs, including NOD1/NOD2 and NLRC4. NOD1 and NOD2 share a same adaptor protein – RIP2 – that is critical for downstream signaling. The CARD domain of RIP2 oligomerizes to form a filamentous structure in responses to activated NOD1-CARD or NOD2-CARD. To investigate the signaling transduction process, the RIP2-CARD oligomeric complex, named RIPosome, was reconstituted and expressed. The structure of filamentous RIP2-CARD complex was resolved at a near-atomic resolution of 3.6 Å. With this high-resolution structure, the mechanism of how two different CARD domains initiate RIP2 oligomerization from NOD1 and NOD2 was demonstrated. Plus, NLRC4-CARD was found to form filamentous oligomers upon activation, with the filament structure solved by a similar method as that for RIP2-CARD filament at 3.3Å resolution. The atomic-resolution structure provides important information reveals the importance of inflammasomes in immune signals transduction.